2017
DOI: 10.1111/cob.12230
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and family‐based obesity treatment: a review of expert recommendations on physical activity in youth

Abstract: What is already known about this subject• Exercise and physical activity are key to the prevention and treatment of childhood obesity.• Family-based approaches are the gold standard for the prevention and treatment of childhood obesity. What does this study add• Expert recommendations for exercise and physical activity for children and adolescents are consistent across numerous professional organizations: 60 min a day of exercise is recommended, with a combination of aerobic, muscle strengthening and bone stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 71 publications
0
61
0
2
Order By: Relevance
“…This fact agrees with a recent systematic review conducted by Iaccarino et al [26], which indicated that most studies performed found no statistically significant differences for weight status, abdominal obesity and adiposity in relation to MD adherence. However, it should be underlined that exploring the relationship between MD and overweight/obesity is complicated, since KIDMED index does not include the frequency of consumption of certain foods, as well as the estimated nutritional intakes derived from this [47].…”
Section: Discussionmentioning
confidence: 99%
“…This fact agrees with a recent systematic review conducted by Iaccarino et al [26], which indicated that most studies performed found no statistically significant differences for weight status, abdominal obesity and adiposity in relation to MD adherence. However, it should be underlined that exploring the relationship between MD and overweight/obesity is complicated, since KIDMED index does not include the frequency of consumption of certain foods, as well as the estimated nutritional intakes derived from this [47].…”
Section: Discussionmentioning
confidence: 99%
“…Those who rate the subject and teacher more highly also demonstrate greater agreement with its management [84], whilst in contrast, also considering it to be less useful. When students conceive PE as sport, they find it more difficult as a subject [85], view it as being more useful, and hold a stronger preference for it [86].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing prevalence of obesity and type 2 diabetes in inactive children with high caloric diets (Foster et al . ) is testament to the general prediction that poor lifestyle results in increased periods of morbidity across the lifespan. If the appearance of disease symptoms is the result of thresholds of function being breached then non‐exercisers, when compared to exercisers, are well on the path to crossing these thresholds much earlier (Fried et al .…”
Section: Introductionmentioning
confidence: 99%